1989
DOI: 10.1128/iai.57.3.711-716.1989
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella haemolytica antigens associated with resistance to pneumonic pasteurellosis

Abstract: Antigens associated with whole Pasteurella haemolytica biotype A serotype 1, a capsular carbohydrateprotein extract of the organism, and P. haemolytica leukotoxin were separated by sodium dodecyl sulfatepolyacrylamide gel electrophoresis. Antigens of the electrophoresed preparations were detected by Western blotting (immunoblotting) with sera from cattle which were either nonvaccinated or vaccinated with live or killed P. haemolytica vaccines and had variable degrees of resistance to experimental pneumonic pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Previous results have demonstrated the surface location of this protein in the E. coli clones (15), and the present data support that observation. There have been a number of reports in the literature on the characterization of outer membrane proteins from P. haemolytica Al and their possible role(s) as protective antigens (6,27). These data were obtained primarily by SDS-PAGE analysis of outer membrane proteins extracted by various methods or by the use of Western immunoblot analysis of the bacterial antigens with immune serum from P. haemolytica Al-infected ani- mals (6,27).…”
Section: Identification Of Ssal As An Outer Membrane Protein Plas-mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results have demonstrated the surface location of this protein in the E. coli clones (15), and the present data support that observation. There have been a number of reports in the literature on the characterization of outer membrane proteins from P. haemolytica Al and their possible role(s) as protective antigens (6,27). These data were obtained primarily by SDS-PAGE analysis of outer membrane proteins extracted by various methods or by the use of Western immunoblot analysis of the bacterial antigens with immune serum from P. haemolytica Al-infected ani- mals (6,27).…”
Section: Identification Of Ssal As An Outer Membrane Protein Plas-mentioning
confidence: 99%
“…There have been a number of reports in the literature on the characterization of outer membrane proteins from P. haemolytica Al and their possible role(s) as protective antigens (6,27). These data were obtained primarily by SDS-PAGE analysis of outer membrane proteins extracted by various methods or by the use of Western immunoblot analysis of the bacterial antigens with immune serum from P. haemolytica Al-infected ani- mals (6,27). However, the identity of these proteins or antigens is often unknown, making it difficult for follow-up and detailed characterization.…”
Section: Identification Of Ssal As An Outer Membrane Protein Plas-mentioning
confidence: 99%
“…Shewen and Wilkie (1988) demonstrated that immunity against M. haemolytica requires leukotoxin (LKT) neutralizing antibodies as well as antibodies against bacterial cell surface antigens. Studies in our and others' laboratories demonstrated that high antibody responses to OMPs, ranging from 16 to 86 kDa, correlated with resistance to challenge with virulent M. haemolytica S1, and vaccination of cattle with OMP-enriched cellular fractions from M. haemolytica S1 enhanced resistance of cattle against experimental challenge (Ayalew et al, 2010(Ayalew et al, , 2011aConfer et al, 2003Confer et al, , 2006Morton et al, 1995;Mosier et al, 1989;Orouji et al, 2012). In this regard, we used immunoproteomics, which uses a combination of 2D-gel electrophoresis (2-DE) and Western blotting with bovine convalescent sera, and identified 132 immunoreactive proteins in outer membrane preparations of M. haemolytica using LC-MS/MS.…”
Section: Introductionmentioning
confidence: 72%
“…A number of P. haemolytica A1 antigens in the 28–31‐kDa range have been suggested to be protective antigens by their correlation with resistance to pneumonic pasteurellosis [18]. Previously we have reported the characterization of three 30‐kDa lipoproteins Plp1, 2 and 3 from P. haemolytica A1.…”
Section: Discussionmentioning
confidence: 99%